Anthropometric techniques in the evaluation of muscle mass of badminton players - Rodriguez, E.; Lara, E.; Berral, C. J.; Berral, F. J. (Archivos de medicina del deporte, 2008)
The quantification of muscle mass is very important, since it is a part of the body mass closely related to health and sport performance. The aim of this study was to determine the muscle mass in badminton players through anthropometric techniques and to identify the most appropriate tetracompartmental division for this population 37 male badminton players from 15 to 19 years old were studied during the X Spanish Championship of Junior Badminton. 55 anthropometric variables were registered, including weigth and hight, skin folds, hights, lenghts, diameters and perimeters according to ISAK norms. The evaluation of muscle mass was obtained by the formulas of Heyms field, Martin, Drinkwater, Doupe and Kerr. The analysis of residual mass and bone mass was done by the Wurch and Von Döbeln equations modified by Rocha, respectively, and the analysis of fat mass was done by Faulkner, Brozek and Siri equations. Results: The equations of Martin Doupe overstimated muscle mass, while that of Hyms field understimated it. The average estimated muscle mass was 44 % of total weight and that of fat mass was 13%. With the six methods of analysis we obtained average values very close to 100 % of the real weight of the athletes. In the following table the percentage of error of he estimated weight in relation to the real weight, measured on a scale, is analyzed. Conclusions: The method of tetracompartmental division that best approached the real weight, as measured on a scale, were the following: residual mass (Würch), bone mass (Rocha), fat mass (Faulkner) and muscle mass (Drinkwater at 98,18%, Kerr at 98,45%).